Literacies in early childhood : changing views, challenging practice - Makin, Laurie; Jones-Diaz, Criss (Eastgardens, N.S.W. : MacLennan + Petty, 2002)
The importance of literacy learning in the first years of school has long been recognised, but literacy experiences in the pre-school years have not always received sufficient attention. In Literacies in Early Childhood: Changing Views, Challenging Practice the authors redress this imbalance, with a focus spanning from birth to eight years. 'Literacy as social practice' is an overriding theme, and it is continually acknowledged that young children's understandings about literacy occur within their cultural and linguistic communities.
Topical and sometimes controversial issues include: the intersections between social identities such as gender, language, ethnicity, 'race', disability and class; the importance of partnerships between educators, families and communities in fostering literacy learning; the impact of visual, technological and commercial influences; the view that children are competent interpreters of their social worlds.
In each chapter 'reflection and follow-up' sections reinforce the link between theory and practice, and examples of children's dialogue, artwork and writing highlight the literary messages conveyed. Readers will find this a compelling text, advocating a broad-minded approach to our observation and facilitation of children's literacy achievements.
1. Literacy as social practice / Jones Diaz and Makin -- 2. Theoretical perspectives in early literacy education: implications for practice / Reid and Comber -- 3. Many roads through many modes: becoming literate in early childhood / Martello -- 4. Language and social practices: everyday talk constructing school-literate practices / Danby -- 5. Literacy transitions / Makin with Groom -- 6. Children as writers / Barratt-Pugh -- 7. Children as readers / Harris -- 8. Authentic literacy assessment / Fleet and Lockwood -- 9. Building on home and community literacy experiences in early childhood education / Spreadbury -- 10. Other words, other worlds: bilingual identities and literacy / Jones Diaz and Harvey -- 11. Indigenous literacies: the case of Maori literacy / Hohepa and McNaughton -- 12. Indigenous literacies: moving vrom social construction towards social justice / Hanlen -- 13. Literacy for all? Young children and special literacy learning needs / McNaught -- 14. Literacy and gender in early childhood contexts: boys on the side? / Alloway and Gilbert -- 15. Technoliteracy and the early years / Hill with Broadhurst -- 16. Literacy, music and the visual arts / Makin and Whiteman -- 17. Children's worlds and critical literacy / Jones Diaz, Beecher and Arthur -- 18. New pathways for literacy in early childhood education / Makin and Jones Diaz.
Includes bibliographical refernces and index.
BIED
Keywords: Literacy -- Study and teaching (Primary); Literacy -- Study and teaching (Preschool); Literacy -- Study and teaching (Early childhood)